First record of the genus Limonium (Plumbaginaceae) from the Malesian region - Nakamura, Koh; Rubite, Rosalio Rivera; Kokubugata, Goro; Yoshiko, Kono; Yokota, Masatsugu; Peng, Ching-I (Phytotaxa, 2013)
The absence of the cosmopolitan genus Limonium Miller (1754: no pagination) (Plumbaginaceae) in the mega-diverse flora of the Malesian region (comprising Brunei Darussalam, Indonesia, Malaysia, Papua New Guinea, the Philippines, and Singapore; Merrill 1923, Ridley 1923, Steenis 1949, Backer & Bakhuizen van den Brink Jr. 1965, Balgooy 1993, Coode et al. 1996, Balgooy 2001, Conn et al. 2004, Chong et al. 2009, Pelser et al. 2011) has intrigued taxonomists and biogeographers since Steenis (1949) noted this. During a field survey as part of the project on floristic and phylogenetic biogeography in the island chain of the Philippines, Taiwan, and southern Japan, we found a population of Limonium in the northern Philippines (Batan Islands) that represents the first record of the genus in the Malesian region. Batan Islands, comprising 10 small (≤ 83.1 km2) oceanic islands, is the northernmost tip of the Malesian region, being ca. 190 km north of Luzon Island of the Philippines and ca. 140 km southeast of Taiwan Island. From the geological location, the present finding suggests that a more extensive survey in Batan Islands may add some more East Asian temperate genera to the flora of the Malesian region, although two enumerations of the early and mid 20th century provide us baseline knowledge of the flora of Batan Islands (Merrill 1908, Hatusima 1966).